P2P architecture over IPv6 for personal internetworking. (2nd August 2006) - Chang, Chi-Yuan; Lin, Fred; Chen, Crota; Chao, Han-Chieh
The purpose of this paper is to study the feasibility of Personal Internetwork (PIN) and find the approach to achieve the real cooperation of multiple personal devices and improve the usability of Hybrid and Pure P2P architecture within a personal scope. We proposed an IPv6 based Node Discovery Stack (NDS) to make the usage of Personal P2P application possible. This paper clarifies the architecture of the PIN and shows how NDS could enhance the personal communication with co-working devices.